Challenges to Internationalization in Russian Higher Education: The Impact of the COVID‑19 Pandemic on the International Student Experience - Maria Abramova; Aleksandra Filkina; Elena Sukhushina (Вопросы образования, 2021)
The COVID‑19 pandemic has essentially jeopardized the internationalization processes in higher education. International travel restrictions, financial insecurities, and the introduction of distance learning formats have been posing serious challenges for international students. The present study is based on data obtained in a countrywide survey of Russian university students conducted in June—July 2021 as part of the project Research and Instructional Design Support for the Development of a Quality Measurement System in Higher Education During the COVID‑19 Pandemic and Beyond. International students’ perceptions of distance learning, its quality and challenges are analyzed. Judging from international students’ responses to the questionnaire, the process of their adaptation to the new study conditions has been routinized. Among the benefits of online learning, international students name the logistic ones such as mobility, relative cost-effectiveness, and optimization of time. Perceptions of the communication constraints related to learning from a distance are largely negative. In addition, international students perceive themselves as a more vulnerable category compared to Russian students and obviously gravitate toward in-person learning. For the most part, international students are ready for blended learning, but remote formats of communication and learning should be applied to them with more caution than with Russian students.